Midwifery Care for Mrs. N Baby Provision of Cord Care Health Education with Wet and Smelly Cord Problems - Achsani Rachmawati; Diah Atmarina Yuliani (Proceedings Series on Health & Medical Sciences, 2024)
Background:One indicator of health status in Indonesia is the infant mortality rate. The third goal of the Sustainable Development Goals (SDGS) is to create a good degree of Health (National Health System) by 2030, namely by ending preventable infant and toddler deaths. Child deaths in Indonesia occur in the newborn (neonatal) period, the first month of life that many are caused by infection. At the time of cutting the umbilical cord and at the time of its treatment before the removal of the umbilical cord can cause tetanus neonaturum. To overcome the occurrence of these infections can be done health education to the public. Health promotion is the process of improving health and socializing to the community in order to increase awareness, willingness and ability as well as the development of an environment that can improve the degree of Health. Method: Case study report using descriptive methods and case analysis. The case study subject was a 6 day old newborn whose umbilical cord was wet and had a slight odor. The time of the case study is February 21 2023, located at Mrs. N, Pekaja RT 05/02 Village, Kalibagor District, Banyumas Regency. Data collection techniques include interviews and secondary studies including documentation and literature studies. Results:The condition of the newborn is generally good, after the umbilical cord care health education to the mother and the demonstration of umbilical cord care to the baby one day later the umbilical cord is dry and loose. Conclusion:Provision of Health Education umbilical cord care is effective in preventing infection in newborns.